Building academic literacy : an anthology for reading apprenticeship - Fielding, Audrey; Schoenbach, Ruth. (San Francisco : Jossey-Bass, 2003)
Publisher's description: Building Academic Literacy: Lessons from Reading Apprenticeship Classrooms, Grades 6-12, features pieces by five middle and high school teachers working with the Reading Apprenticeship instructional framework introduced in Reading for Understanding, (Schoenbach, et al, Jossey-Bass, 1999). Filled with instructional tips, lesson plans, and curriculum resources, this book offers guidance on conducting Academic Literacy courses as well as readings from a companion student book-- Building Academic Literacy: An Anthology for Reading Apprenticeship. It can serve as an excellent resource for any content area teacher, grades 6-12, looking for classroom-based ideas to motivate adolescents in becoming more active, engaged and strategic readers.
Includes bibliographical references (p. 267-268).
Keywords: Reading (Secondary) -- United States -- Case studies. -- Curricula; Developmental reading -- United States -- Case studies; Literacy -- Social aspects -- United States